Evolutionary Trajectories of Complex Traits in European Populations of Modern Humans - Kuijpers, Yunus; Domínguez-Andrés, Jorge; Bakker, Olivier B.; Gupta, Manoj Kumar; Grasshoff, Martin; Xu, Cheng-Jian; Joosten, Leo A.B.; Bertranpetit, Jaume; Netea, Mihai G.; Li, Yang (Frontiers in Genetics, 2022)
Humans have a great diversity in phenotypes, influenced by genetic, environmental, nutritional, cultural, and social factors. Understanding the historical trends of physiological traits can shed light on human physiology, as well as elucidate the factors that influence human diseases. Here we built genome-wide polygenic scores for heritable traits, including height, body mass index, lipoprotein concentrations, cardiovascular disease, and intelligence, using summary statistics of genome-wide association studies in Europeans. Subsequently, we applied these scores to the genomes of ancient European populations. Our results revealed that after the Neolithic, European populations experienced an increase in height and intelligence scores, decreased their skin pigmentation, while the risk for coronary artery disease increased through a genetic trajectory favoring low HDL concentrations. These results are a reflection of the continuous evolutionary processes in humans and highlight the impact that the Neolithic revolution had on our lifestyle and health.